ANALISIS PENGAKUAN PENDAPATAN DAN BEBAN KONTRAK KONTRUKSI PADA CV. TARUNA - Benny Saputra; Masiyah Kholmi; Endang Dwi Wahyuni (Universitas Gajayana Malang, 2018)
Abstract: The purpose of this research is to analyze the Tecognition of income and expenses on the G.V. Taruna by adjusting its the method stated in the standard statement of financial accounting number 34. There are two methods of recognition of income in PSAK No. 34 namely the completed contract method and completion percentage method. The research method used is descriptive method with interview data collection techniques and documentation. Based on the results of data analysis shows war the recognition of income and expenses is not in accordance with financial accounting statement number 34 because in the recording of advances received by the company recorded as income and recording of costs incurred only during the project period only recorded in the daily cash book and the results of the recording have not been journalized,